LOW CITIZEN E-PARTICIPATION WITHIN THE BEKASI NYAMBUNG BAE COMPLAINT SERVICE IN BEKASI REGENCY - Syifa Annisa Yaniar (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
Bekasi Nyambung Bae (BEBUNGE) application is an implementation of E-Governance Innovation, which was designed by Bekasi Regency Information, Coding and Statistics Communication Service through Bekasi Regent Regulation Number 42 of 2020 and Bekasi Regent Regulation Number 51 of 2018. This study is about researchers' analysis of the inefficiencies observed in BEBUNGE online complaint service, which marked its third year in operation in August 2023. Despite its intended purpose of facilitating the reporting of urgent matters for the residents of Bekasi Regency, the research sheds light on the service's shortcomings and inefficiencies. Researchers used e- participation theory in the context of e-governance, and e-government concepts to identify problems and findings in e-governance development through BEBUNGE. The object of this research is the low percentage of resolved complaint reports as a form of inefficiency in the public complaint service on BEBUNGE application which is managed by Bekasi Regency Information, Coding and Statistics Communication Service bureaucracy. The research method used is a qualitative approach with a case study research design which was analyzed descriptively. The novelty of this research is associated with the inefficiencies in BEBUNGE complaint service, specifically addressing the low level of electronic participation in Bekasi Regency. The research results show that there is a lack of employees supervising BEBUNGE, which causes uneven coordination. To overcome this problem, they must integrate e-participation, conducting formal socialization campaigns, partnering with key bureaucracies, and collaborating with Non-Governmental Organizations (NGOs). This strategic approach targets challenges arising from a limited workforce, aiming to enhance coordination for more effective application management.